Role of Genetic Variation in ABC Transporters in Breast Cancer Prognosis and Therapy Response - Hlaváč, Viktor; Václavíková, Radka; Brynychová, Veronika; Koževnikovová, Renata; Kopečková, Katerina; Vrána, David; Gatěk, Jiří; Souček, Pavel (International journal of molecular sciences, 2020)
Breast cancer is the most common cancer in women in the world. The role of germline genetic variability in ATP-binding cassette (ABC) transporters in cancer chemoresistance and prognosis still needs to be elucidated. We used next-generation sequencing to assess associations of germline variants in coding and regulatory sequences of all human ABC genes with response of the patients to the neoadjuvant cytotoxic chemotherapy and disease-free survival (n = 105). A total of 43 prioritized variants associating with response or survival in the above testing phase were then analyzed by allelic discrimination in the large validation set (n = 802). Variants in ABCA4, ABCA9, ABCA12, ABCB5, ABCC5, ABCC8, ABCC11, and ABCD4 associated with response and variants in ABCA7, ABCA13, ABCC4, and ABCG8 with survival of the patients. No association passed a false discovery rate test, however, the rs17822931 (Gly180Arg) in ABCC11, associating with response, and the synonymous rs17548783 in ABCA13 (survival) have a strong support in the literature and are, thus, interesting for further research. Although replicated associations have not reached robust statistical significance, the role of ABC transporters in breast cancer should not be ruled out. Future research and careful validation of findings will be essential for assessment of genetic variation which was not in the focus of this study, e.g., non-coding sequences, copy numbers, and structural variations together with somatic mutations.
Keywords: nádorové biomarkery; Prognosis; alely; Biomarkers, Tumor; ATP-Binding Cassette Transporters; nádory prsu; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Neoadjuvant Therapy; Gene Frequency; Genotype; genetická variace; ABC transportéry; Kaplanův-Meierův odhad; Breast Neoplasms; prognóza; lokus kvantitativního znaku; neoadjuvantní terapie; vysoce účinné nukleotidové sekvenování; výsledek terapie; frekvence genu; Treatment Outcome; ženské pohlaví; Female; Genetic Variation; jednonukleotidový polymorfismus; genotyp; lidé; Polymorphism, Single Nucleotide; Quantitative Trait Loci; High-Throughput Nucleotide Sequencing; Kaplan-Meier Estimate; Alleles